Vietnam civil aviation Law - The National Assembly (2006)
This Law provides for civil aviation activities, covering aircraft, airports, airfields, aviation personnel, air navigation, air carriage, aviation security, civil liability, general aviation and other activities related to civil aviation. Law does not provide for activities of official -duty aircraft, including military aircraft, specialized aircraft of customs and police forces and other aircraft used for state-duty purposes, except for cases where official-duty aircraft are used for civil purposes or other cases prescribed in the Vietnam Civil Aviation Law.